2018
DOI: 10.1002/hbm.24469
|View full text |Cite
|
Sign up to set email alerts
|

Neural gain control measured through cortical gamma oscillations is associated with sensory sensitivity

Abstract: Gamma oscillations facilitate information processing by shaping the excitatory input/output of neuronal populations. Recent studies in humans and nonhuman primates have shown that strong excitatory drive to the visual cortex leads to suppression of induced gamma oscillations, which may reflect inhibitory-based gain control of network excitation. The efficiency of the gain control measured through gamma oscillations may in turn affect sensory sensitivity in everyday life. To test this prediction, we assessed th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 63 publications
7
39
0
Order By: Relevance
“…In a majority of these clinically oriented studies, the parameters of gamma oscillations (power, frequency) were investigated in a single experimental condition. Our present and previous [18,71,76] results suggest that changes of gamma parameters caused by changes in sensory input intensity may be particularly informative for detecting E-I balance abnormalities in neuro-psychiatric disorders.…”
Section: Gr Suppression Transition Point and E-i Balance In The Visuasupporting
confidence: 67%
See 1 more Smart Citation
“…In a majority of these clinically oriented studies, the parameters of gamma oscillations (power, frequency) were investigated in a single experimental condition. Our present and previous [18,71,76] results suggest that changes of gamma parameters caused by changes in sensory input intensity may be particularly informative for detecting E-I balance abnormalities in neuro-psychiatric disorders.…”
Section: Gr Suppression Transition Point and E-i Balance In The Visuasupporting
confidence: 67%
“…In indirect support of this assumption, we have recently described a lack of velocity-related gamma suppression in a subject with epilepsy and occipital spikes [18]. A link between reduced velocityrelated GR suppression and sensory hypersensitivity [71] further supports this conjecture.…”
Section: Gr Suppression Transition Point and E-i Balance In The Visuamentioning
confidence: 62%
“…To better quantify this effect, we separated the gamma response into three frequency bands -low (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40), mid (40-70 Hz) and high (70-100 Hz)-based on the data from Experiment 1. We then calculated the average amplitude for each condition within a time window of 0-16 s (Fig 10) and analysed this data as a two-factor repeated-measures design for each frequency band ( Table 5).…”
Section: Plos Onementioning
confidence: 99%
“…Visual stimulus induced gamma oscillations are a prominent feature of the local field potential in the visual cortex, and have been observed in humans [1][2][3], non-human primates [4][5][6], cats [7,8] and rodents [9,10], suggesting that they represent a fundamental aspect of the operation of the visual cortex that has been preserved across species. Gamma oscillations are sensitive to the presence of luminance contrast in the visual field [2,5,[11][12][13][14][15] and are tuned to properties of luminance-defined gratings, such as their size [16][17][18], orientation [13,19] and spatial and temporal frequency [1,[20][21][22][23][24][25]. However there is some debate about the extent to which they are generated by more naturalistic stimuli [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…A weak suppression of gamma oscillations at high stimulation intensities may then result in a stronger impact of the sensory stimulation on the neural network, and lead to sensory overload. Indeed, in a recent study, we have found that a weaker suppression of gamma response at fast motion velocities (of high-contrast gratings) correlated with enhanced sensory sensitivity, especially in the visual domain (Orekhova et al, 2018a).…”
Section: Discussionmentioning
confidence: 87%